PENERAPAN SISTEM INVENTORY LABOTARIUM DIGITAL DENGAN METODE CRITICAL SUCCES FACTOR PADA PERGURUAN TINGGI RAHARJA - Khanna Tiara; Dewi Immaniar; Fiqih Arzia (CCIT Journal, 2015)
The system supplies the right stuff and fit is important for College field in terms of the preparation of Perguruan Tinggi Raharja and loaning stuff on the computer systems Laboratory (Lab. Digital). Lab. Digital Perguruan Tinggi Raharja is used to perform testing, scientific research, education, practice and research. Lab. Digital is equipped with the tools needed to support the activities that are carried out so that the need for the process of recording of inventory of existing equipment in the Lab. sk. this process it is important to monitor or monitor the condition of the existing equipment. The process of recording data inventory equipment Lab. Digital still performed manually has some drawbacks, namely in terms of storage and retrieval. If the goods supplied on Lab. Digital not groomed properly then the goods will be lost and many are not well maintained, in this regard are also not recorded properly on the Lab. SK Perguruan Tinggi Raharja would suffer losses as a result of monitoring the preparation did not go well. This has been the rationale of how making an inventory system so ease Perguruan Tinggi Raharja for monitoring data collection, monitoring of loan items of goods and the creation of reports in the Lab. Digital it is possible to use a combination of using the method of analysis of CSF (Critical Success Factor) as an attempt to interpret objective explicitly to specify the activities that must be performed and what information is needed. And by making the system inventory can be seen 4 conditions of goods if the goods arelost, damaged, or expired good so that it can monitor inventory items in a Lab. Digital Perguruan Tinggi Raharja